Emerging flexible and wearable physical sensing platforms for healthcare and biomedical applications - Kenry; Yeo, Joo Chuan; Lim, Chwee Teck (Microsystems & nanoengineering, 2016)
There are now numerous emerging flexible and wearable sensing technologies that can perform a myriad of physical and physiological measurements. Rapid advances in developing and implementing such sensors in the last several years have demonstrated the growing significance and potential utility of this unique class of sensing platforms. Applications include wearable consumer electronics, soft robotics, medical prosthetics, electronic skin, and health monitoring. In this review, we provide a state-of-the-art overview of the emerging flexible and wearable sensing platforms for healthcare and biomedical applications. We first introduce the selection of flexible and stretchable materials and the fabrication of sensors based on these materials. We then compare the different solid-state and liquid-state physical sensing platforms and examine the mechanical deformation-based working mechanisms of these sensors. We also highlight some of the exciting applications of flexible and wearable physical sensors in emerging healthcare and biomedical applications, in particular for artificial electronic skins, physiological health monitoring and assessment, and therapeutic and drug delivery. Finally, we conclude this review by offering some insight into the challenges and opportunities facing this field. Nanosensors: Flexible future for medical technology Flexible and wearable sensors show promise for healthcare and biomedical applications. Chwee Teck Lim and his co-workers at the National University of Singapore review recent research into wearable sensors and their potential for medical science. Tiny sensors that monitor physiological details about the body at the microscopic scale could generate health data, and provide insights into the health status or even progression of disease. Despite the many inherent challenges in developing stable and robust sensors for flexible structures, the team are encouraged by recent advances in this field. Some examples include: ( 1 ) electronic skins that can sense environmental factors, such as temperature, for possible use as skin substitutes or for real-time monitoring of physiological signals, ( 2 ) devices for monitoring organs which could detect and map diseased tissues, and ( 3 ) neural implants that sense and interact with the central nervous system to restore the use of paralyzed limbs.